Bioassays quantifying the adverse effects of three strains of the harmful dinoflagellate Alexandrium pseudogonyaulax and goniodomins (GDs) on the viability and membrane integrity of the RTgill-W1 cell line of the rainbow trout (Oncorhynchus mykiss) - Kristof Möller; Urban Tillmann; Magdalena Pöchhacker; Elisabeth Varga; Bernd Krock; Florian Koch; Thomas M Harris; Cédric Léo Meunier (PANGAEA, 2024)
RTgill-W1 gill cells of the rainbow trout (Oncorhynchus mykiss) were subjected to supernatants from exponentially grown Alexandrium pseudogonyaulax cultures or to purified goniodomins (GDs) for 24 h to create dose-response curves. The bioassays were carried out with 300 uL of total incubation volume in 96 well plates for everything except the goniodomins. Here the starting incubation volume was only 100 uL. After 24 hours, 50 μl subsamples were transferred to a new 96-well plate for the assessment of lytic activity using a lactate dehydrogenase (LDH) cytotoxicity assay kit (CyQUANT™, Thermo Fisher Scientific, C20301) following the standard protocol provided by the manufacturer. Subsequently, residual supernatants or goniodomins were thoroughly siphoned off and the metabolic activity of the remaining gill cells was assessed using a cell viability assay kit (CellTiter-Blue®, Promega, G8080) following the standard protocol provided by the manufacturer. Both assays were analysed fluorometrically using a cell-imaging multi-mode reader (Cytation™ 3 Cell Imaging Multi-Mode Reader, BioTek). All data was pre-filtered according to (1) visual inspection of the gill cell densities in the 96-well plates and if densities differed greatly data was excluded, and (2) data were grouped by each biological gill cell line replicate, each biological A. pseudogonyaulax replicate, each strain and each cell density equivalent or goniodomin concentration and subjected to a Dixon outlier test. If the Dixon test was significant, data was excluded. These datasets contain a minimum of four biological gill cell line replicates tested with three different A. pseudogonyaulax strains, each comprised of up to three biological replicates. Each biological replicate of each A. pseudogonyaulax strain was tested with a total of three to five cell density equivalents of cell-free supernatants, each comprised of two to six technical replicates. In addition, two to three biological gill cell replicates were tested at four concentrations of GDA, GDA-sa or GDA + GDA-sa each comprised of three technical replicates. The bioassays were carried out between May 19 and October 10, 2023 at the Department of Food Chemistry and Toxicology (LMC), Faculty of Chemistry, University of Vienna.